The ACORDAR project: Agribusiness relationships that highlighted the power of establishing links (Introductory document) - Mosquera Echeverry, Erika Eliana (Catholic Relief Services, 2012)
Five years of fieldwork, more than 52 million dollars invested, nearly 200 organizations working together in alliances, 50 municipalities covered (one-third of Nicaragua’s municipalities), 25 local governments that invested more than 20 million dollars in the strengthening of value chains, 7711 farm families benefitted, 27,396 permanent jobs generated, a 20% increase in income, 222,760 tons of food produced, more than 128 million dollars in sales, more than 100 professionals contributing knowledge and expertise, and a monitoring and evaluation system that has served as model for other initiatives make the Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships (ACORDAR) an unprecedented project in this Central American country. This brief presents the results of the participative capitalization process (for topics such as cacao, coffee, beans, fruits and vegetables, roots, and Municipal and Agribusiness development), funded by USAID